PROFILE OF CREATIVE THINKING SKILLS AND STUDENT LEARNING OUTCOMES IN PROJECT-BASED SCIENCE LEARNING - Pabrianto; Fenny Roshayanti; Joko Siswanto (Indonesian Journal of Education (INJOE), 2022)
National education requires students to have the ability to think creatively, especially exact subjects such as physics. The purpose of this study is to determine the profile of creative thinking of grade VII students of SMPN 10 Teluk Keramat on material for changing the form of objects for the 2020/2021 school year. The subjects of this study were grade VII students of SMPN 10 Teluk Keramat consisting of two classes A and B totaling 56 students. The research method used is the descriptive method. The variable of this study is the ability to think, namely creative thinking which is measured using a written test in the form of essay questions. Data collection uses questions developed from four creative thinking indicators, each question is given a score of 1-4 with the criteria of each indicator. Based on the results of the study, the creative thinking ability of grade VII students of SMPN 11 Teluk Keramat is 8.69 (15.51%) from a maximum score of 14. It can be seen from the ability of students based on the indicators of fluency 2.25 (33.92%), Flexibility 02.64 (58.92%), Originality 1.87 (53.57%) and Elaboration 1.87 (64.24%). The results of students' creative thinking ability are still lacking. Therefore, students' creative thinking skills need to be improved in the learning process